1990
DOI: 10.1212/wnl.40.7.1067
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of neurologic disease associated with anti‐GM 1 antibodies

Abstract: We compared anti-GM1 IgM antibody titers in patients with various neurologic diseases and in normal subjects. We found increased titers in patients with lower motor neuron disease, sensorimotor neuropathy, or motor neuropathy with or without multifocal conduction block. In patients with other diseases, titers are similar to those in normal individuals, suggesting that anti-GM1 antibody levels are not increased nonspecifically after neural injury or inflammatory diseases. Anti-GM1 antibodies in many of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
2
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(93 citation statements)
references
References 0 publications
1
86
2
3
Order By: Relevance
“…While no viruses causative of meningitis weredetected in either the blood or CSFin our case, the herpes simplex virus is the most common virus responsible for concurrent acute urinary retention and meningitis (7,8), probably because of its neurotropic nature or its reactivation from ganglionic latency (3-6, 10, 1 1). A few studies have suggested post-infectious-immune-mediated demyelination as a cause of neurogenic bladder (1 1), but anti-GM, ganglioside antibody, which plays a principal role in demyelination in autoimmunemotor neuropathy ( 14), was not detected in our case. Since the following conditions such as psychogenic urinary retention, the first manifestation of multiple sclerosis, drug intoxication, lumbosacral disc protrusion, and rheumatological disorders must all be considered in the differential diagnosis of acute urinary retention in a healthy young individual (1-3, 5, 10, 12), it is essential to promptly examine the CSF (1,3,12) and to test for viruses, especially by means of nucleic acid amplification (9, ll), to examine the central nervous system by magnetic resonance imaging, and to test for autoimmune abnormalities in addition to a careful review of the patient's history and physical examination.…”
Section: Discussioncontrasting
confidence: 51%
“…While no viruses causative of meningitis weredetected in either the blood or CSFin our case, the herpes simplex virus is the most common virus responsible for concurrent acute urinary retention and meningitis (7,8), probably because of its neurotropic nature or its reactivation from ganglionic latency (3-6, 10, 1 1). A few studies have suggested post-infectious-immune-mediated demyelination as a cause of neurogenic bladder (1 1), but anti-GM, ganglioside antibody, which plays a principal role in demyelination in autoimmunemotor neuropathy ( 14), was not detected in our case. Since the following conditions such as psychogenic urinary retention, the first manifestation of multiple sclerosis, drug intoxication, lumbosacral disc protrusion, and rheumatological disorders must all be considered in the differential diagnosis of acute urinary retention in a healthy young individual (1-3, 5, 10, 12), it is essential to promptly examine the CSF (1,3,12) and to test for viruses, especially by means of nucleic acid amplification (9, ll), to examine the central nervous system by magnetic resonance imaging, and to test for autoimmune abnormalities in addition to a careful review of the patient's history and physical examination.…”
Section: Discussioncontrasting
confidence: 51%
“…However, they do not increase nonspecifically after neural injury or inflammatory disease. 9 The mechanism of molecular mimicry with anti-GM1-antibodies has been suggested in one other case report about ATM. In this case the myelopathy was part of an antiphospholipid syndrome and was triggered by a pinworm infestation (E. vermicularis).…”
Section: Discussionmentioning
confidence: 94%
“…The sera were all frozen at -30°C until use. Weexamined serum IgM and IgG anti-GMl, GDlb, GQlb, GDla, GTlb, GM2 and GTla antibodies by ELISA according to the previous method (29) had IgG or IgM anti-GMl, GDlb, GQlb or GM2 antibodies. One patient had only IgG anti-GDla antibodies and the other only IgG anti-GTla antibodies.…”
Section: Elisamentioning
confidence: 99%